Perdagangan Berjangka Komoditi Dalam Perspektif Analisis Usul Fiqh - Fatum, Fatum (UIN Sunan Kalijaga, 2013)
In the realm of classical fiqh, we know the “sal?m”, a contract ordering an item with agreed criteria and with a cash payment when the contract is executed. Futures Contracts are kind of buying and selling the “indicated” in the category of sal?m. Substance which is slightly different with regards, born in non-Muslim countries, and the fact that this practice is quite common place in Indonesia, making Futures Contracts interesting to study. The question that eventually arises is, “how u??l fiqh view this practice?” The questions will be, “whether this practice is allowed by Islam?” This paper seeks to answer the question.